Folding and aggregation energy landscapes of tethered RRM domains of human TDP-43 are coupled via a metastable molten globule-like oligomer - Pillai, Meenakshi; Jha, Santosh Kumar (Biochemistry, 2019)
Stress-induced misfolding and intraneuronal aggregation of the highly conserved nucleic acid binding protein TDP-43 (transactive response DNA binding protein 43 kDa) and its fragments have been implicated in amyotrophic lateral sclerosis and several other neurodegenerative diseases. However, the physicochemical mechanism of its misfolding from the functional folded state is poorly understood. TDP-43 is a four-domain protein and performs the essential nucleic acid binding function with the help of its two tandem RNA recognition motif domains naturally tethered by a linker (called here the tethered RRM domain of TDP-43 or TDP-43(tRRM)). Here, we show that the monomeric native form of TDP-43(tRRM) remains in a pH-dependent and reversible thermodynamic equilibrium with a protonated, nanosized, 40-merit form (the A form). Under the stress-like low-pH condition, the A form becomes predominantly populated. In the A form, protein molecules have restricted dynamics of surface side-chain residues but native-like secondary structure. This self-assembled form possesses a loosely packed core in which the intrinsically disordered and aggregation-prone regions are in the proximity. The A form is metastable and swiftly aggregates into a highly stable amyloid-like protofibrillar form (beta form) mediated by the disorder-to-order transition of intrinsically disordered regions upon small environmental perturbations. Interestingly, the A form and the beta form are not formed when TDP-43(tRRM) is bound to DNA, indicating that the nucleic acid binding regions of the protein participate in their formation. Our results reveal how the energy landscapes of folding and aggregation of TDP-43(tRRM) are coupled by a metastable molten-globule like oligomeric form and modulated by stress-like conditions.